2011
DOI: 10.1021/nn201331n
|View full text |Cite
|
Sign up to set email alerts
|

In VitroPolymerization of Microtubules with a Fullerene Derivative

Abstract: Fullerene derivative C(60)(OH)(20) inhibited microtubule polymerization at low micromolar concentrations. The inhibition was mainly attributed to the formation of hydrogen bonding between the nanoparticle and the tubulin heterodimer, the building block of the microtubule, as evidenced by docking and molecular dynamics simulations. Our circular dichroism spectroscopy measurement indicated changes in the tubulin secondary structures, while our guanosine-5'-triphosphate hydrolysis assay showed hindered release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 46 publications
(80 reference statements)
1
44
0
1
Order By: Relevance
“…Upon the formation of AgNP-HSA corona, the percent of a-helices was reduced while that of b-sheets was increased in the HSA secondary structures, possibly resulting from breakage of the hydrogen bonds between neighboring ahelices and configuration of new, sterically less ordered hydrogen bonds between the a-helices and the citrate coating of the AgNPs, similarly to that observed for tubulins exposed to a fullerene derivative. 31 As shown in the CD measurement, the presence of lipid vesicles alleviated the conformational changes of the proteins induced by the nanoparticles, likely due to the electrostatic repulsion between the vesicles and the nanoparticles. Conversely, the GP measurement demonstrated that both nanoparticles and protein corona interacted with lipid vesicles to enhance fluidity of the latter, although free proteins did not exert much effect on the vesicle conformation.…”
mentioning
confidence: 78%
“…Upon the formation of AgNP-HSA corona, the percent of a-helices was reduced while that of b-sheets was increased in the HSA secondary structures, possibly resulting from breakage of the hydrogen bonds between neighboring ahelices and configuration of new, sterically less ordered hydrogen bonds between the a-helices and the citrate coating of the AgNPs, similarly to that observed for tubulins exposed to a fullerene derivative. 31 As shown in the CD measurement, the presence of lipid vesicles alleviated the conformational changes of the proteins induced by the nanoparticles, likely due to the electrostatic repulsion between the vesicles and the nanoparticles. Conversely, the GP measurement demonstrated that both nanoparticles and protein corona interacted with lipid vesicles to enhance fluidity of the latter, although free proteins did not exert much effect on the vesicle conformation.…”
mentioning
confidence: 78%
“…Circular dichroism (CD) is a widely used technique to characterize the conformational change of proteins in solution. CD is especially powerful to quantify partial conformational changes of proteins, which is very common upon protein binding on NP surfaces 26, 39. Intrinsic fluorescence of proteins is a natural probe for investigating binding specificity of proteins with NPs, because only Trp (strong) and Tyr residues are fluorescent (Phe is very weak), and their fluorescence can be distinguished by exciting at both 280 nm and 295 nm 26.…”
Section: Protein–np Interactionsmentioning
confidence: 99%
“…Фуллеренол C 60 (OH) 20 образует комплекс вклю-чения с белками микротрубочек, основного компо-нента цитоскелета [46]. Фуллеренол ингибировал полимеризацию микротрубочек при низких микро-молярных концентрациях, образуя комплекс вклю-чения фуллеренол -тубулин (9 : 1).…”
Section: фуллерен и биологические молекулыunclassified